- - Lolas Stepke, Fernando (Acta Bioethica, 2000)
This article proposes the concepts of legality and legitimacy to the ethical analysis of medical publications. Legality refers to the compliance with procedures accepted by the scientific community related to validity, reliability, and solvency of the research work. Legitimacy alludes to the properness with which ethical principles are dealt with within the contents of the publication. This analysis is especially relevant in studies concerning human subjects, but it is not restricted to them. Together with emphasizing the scientific editor’s role as "gatekeeper" of legality and legitimacy, a taxonomy of scientific publications in terms of its character, style and audience is proposed. The importance of bioethical examining of publication practices lies in that they reflect the condition of medical discipline, the social respect and the possibility of maintaining it. The fact that written regulations reflect aspirations and suggestions is underlined, and accordingly, it is deemed as erroneous to conceive them as mandatory. Safeguarding of the ethical nature of the publications can only be made possible by educating researchers on their commitments and obligations.